Analysis The Value of Tauhid Education Contained in Mas Ronggasasmita’s Suluk Wejang - Novita Setyowati; Fauzi Muharom (Ijtimā iyya Journal of Muslim Society Research, 2021)
The research was conducted with the aim of analyzing the values of tauhid education contained in Mas Ronggasasmita’s Suluk Wejang, then applying the values contained, including the Oneness of Allah, belief in the existence of Allah, straightening intentions, always repenting, being as much as zuhud and wara’, patient and sincere, dependent and trusting in Allah, gratitude and pleasure, good heart and character, perfection belongs only to Allah, being a knowledgeable, intelligent and faith, having a perfect teacher, believing in the names and attributes of Allah, always remembering death. The application of these values by instilling the real meaning of laa ilaaha illallahu in living daily life, not just mere pronunciation. Students are given by Allah various potentials in living a life whose ultimate goal is to reach Allah the Creator Keywords: values, tauhid education, Suluk Wejang